Masses, crowds, communities, movements: Collective formations in the digital age - Ulrich Dolata; Jan Felix Schrape (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2014)
From prosumers to swarms, crowds, e-movements and e-communities, the Internet allows for new forms of collective behavior and action anywhere on the spectrum between individuals and organizations. In all of these cases, online technologies function as connectivityenhancing tools and have prompted the search for novel or inherently different collective formations and actors on the web. However, research to date on these new collective formations on the web lacks a sociologically informed and theoretical focus. Instead, loosely defined terms such as "swarm", "crowd" or "network" are readily used as a catch-all for any formation that cannot be characterized as a stable corporate actor. Such terms contribute little to an understanding of the vast range of collective activities on the Internet, namely because the various collective formations differ significantly from each other with regard to their size, internal structure, interaction, institutional dynamics, stability and strategic capability. In order to bridge this gap, this study investigates two questions: One, how might the very differently structured collectives on the Internet be classified and distinguished along actor- or action-centered theory? And two, what influence do the technological infrastructures in which they operate have on their formation, structure and activities? For this we distinguish between two main types of collectives: non-organized collectives, which exhibit loosely-coupled collective behavior, and collective actors with a separate identity and strategic capability. Further, we examine the newness, or distinctive traits, of online-based collectives, which we identify as being the strong and hitherto non-existent interplay between the technological infrastructures that these collectives are embedded in and the social processes of coordination and institutionalization they must engage in in order to maintain their viability over time. Conventional patterns of social dynamics in the development and stabilization of collective action are now systematically intertwined with technology-induced processes of structuration. – – Dieses Discussion Paper geht den beiden Fragen nach, wie sich die sehr unterschiedlich strukturierten kollektiven Gebilde im Internet - beispielsweise Swarms, Crowds, Social Networks, E-Communities, E-Movements - akteur- bzw. handlungstheoretisch einordnen und voneinander abgrenzen lassen und welchen Einfluss die technologischen Infrastrukturen, in denen sie sich bewegen, auf ihre Entstehung, Strukturierung und Aktivität haben. Dazu wird zunächst zwischen zwei wesentlichen Varianten kollektiver Formationen unterschieden, die als nicht-organisierte Kollektive und als strategiefähige kollektive Akteure charakterisiert werden. Daran anknüpfend wird herausgearbeitet, was das Neue ist, das kollektive Formationen im Internet auszeichnet: Es besteht in einer so zuvor nicht gekannten Verschränkung nach wie vor unverzichtbarer sozialer Konstitutions-, Koordinations- und Institutionalisierungsprozesse mit den technischen Infrastrukturen, die das Netz bietet. Klassische soziale Entstehungs- und Organisierungsmuster kollektiven Verhaltens bzw. Handelns mischen sich im Online-Kontext systematisch mit eigenständigen technischen Strukturierungsleistungen.
Keywords: 300